Strongly \({g^{*}}\)-Closed Graph Function with Strongly-\({T_{i}{^{g^{*}}}}\) Spaces (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we introduce the graph function called Strongly \(g^{*}\)-closed graph function and studied some of their properties.
Keywords: Strongly \(g^{*}\)-closed graph function